Identifying of rational conditions for etherification of sunflower soapstock fatty acids - Birta, Gabriella; Levoshko, Nadiya; Knysh, Vladyslav; Usenko, Svitlana; Shostia, Anatolii; Ovsiannikova, Tetiana; Falalieieva, Tetiana; Marushko, Larysa; Semenko, Yevhen; Zygin, Sergii (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the process of esterification of sunflower soapstock fatty acids with butanol. Soapstock is a waste of the oil and fat industry, which is formed in the process of alkaline neutralization of oils. The processing of soapstock to obtain fatty acids is promising, since the disposal of waste is difficult and dangerous, and fatty acids are an industrially valuable product. Fatty acids obtained from soapstock are an available raw material for the production of fatty acid esters of low molecular weight alcohols, which are the basis of alternative biodiesel fuel. The influence of the conditions of esterification of fatty acids from sunflower soapstock (CAS Number 61788-66-7) with butanol (CAS Number 71-36-3) in the presence of an alkylbenzenesulfonic acid catalyst on the acid value of the reaction mixture was studied. This indicator reflects an increase in the content of butyl esters. The fatty acids used, obtained from soapstock by decomposition with sulfuric acid, meet the requirements of DSTU 4860 for first-grade fatty acids. The neutralization number of fatty acids is 186.0 mg KOH/g, the mass fraction of moisture and volatile substances is 1.7 %, the mass fraction of total fat is 97.5 %, the depth of cleavage is 67.1 % of oleic acid. Rational conditions for the esterification process have been established, which correspond to the maximum reduction in the acid value of the reaction mixture: duration is 12 hours, catalyst concentration is 3.5 %. In this case, the acid value of the reaction mass was 4.05 mg KOH/g. The product yield was 91.5 %. Product parameters: mass fraction of esters – 92.7 %, mass fraction of total glycerol – 0.20 %, mass fraction of moisture 0.04 %, density at the temperature of 15 °C – 840 kg/m3. The results obtained make it possible to obtain a high-quality base for biodiesel fuel using soapstock fatty acids under rational conditions